Bargaining with a bank - Thomas Mosk (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
This paper examines bargaining as a mechanism to resolve information problems. To guide the analysis, I develop a parsimonious model of a credit negotiation between a bank and firms with varying levels of impatience. In equilibrium, impatient firms accept the bank's offer immediately, while patient firms wait and negotiate price adjustments. I test the empirical predictions using a hand-collected dataset on credit line negotiations. Firms signing the bank's offer right away draw down their line of credit after origination and default more than late signers. Late signers negotiate price adjustments more frequently, and, consistent with the model, these adjustments predict better ex post performance.
urn:nbn:de:hebis:30:3-466774
Keywords: G21; G32; 330; Credit lines; Contract terms; Bargaining; Screening